Soucasný stav testování chemorezistence nádorů ex vivo v Masarykove Onkologickém Ustavu v Brne - Poprach, A; Michalová, E; Pavlík, T; Lakomy, R; Vyskocil, J; Nemeccek, R; Zaloudík, J; Vyzula, R; Kocák, I; Kocáková, I (Klinicka onkologie, 2008)
Chemoresistance assay results may play a role in cancer management decision process. Since August 2006 testing chemoresistance has been tested according to a protocol that was designed for this reason in our institute (Masaryk Memorial Cancer Institute). Five groups of different types of cancer in particular clinical stages were defined for chemosensitivity testing with: (1) metastatic malignant melanoma, (2) soft tissue sarcoma (STS), either primary or recurrent/metastic, (3) primary or metastatic renal cancer, (4) recurrent ovarian cancer and (5) other diagnosis "on clinician's request". In the period from September 2006 to November 2007, 25 samples of malignant melanoma (reproducible results in 9 cases), 29 samples of STS (relevant data in 11 cases), 36 samples of renal cancer (relevant results in 20 samples) and 16 samples of ovarian cancer (reproducible results in 11 cases) were acquired. Sensitivity to certain chemotherapy agent observed ex vivo does not necessarily mean that the cancer would also be sensitive to the same agent in vivo, however, ex vivo resistance with following in vivo sensitivity of the tumour has not been observed to date. The cultivation of malignant cells is very uncertain in solid tumours, which consist of several malignant cell multiclones (benign/stromal cells may outgrow malignant cells). This cultivation uncertainty as well as the unique complexity of human metabolism makes clinical application of chemoresistance testing at least very questionable. The small number of successfully evaluated samples has not yet provided us to carry out proper statistical evaluation and clinical application.
Keywords: Kidney Neoplasms; Drug Resistance, Neoplasm; Drug Screening Assays, Antitumor; nádory ledvin; nádory vaječníků; Sarcoma; lidé; sarkom; Female; melanom; Ovarian Neoplasms; chemorezistence; ženské pohlaví; screeningové testy protinádorových léčiv; Melanoma; Humans